Lifestyle Analysis on Purchasing Decisions Through Price Perception as a Mediating Variable - Haq, Qubaila Nurul; Ramdan, Asep Muhamad; Mulia Z, Faizal (Dinasti International Journal of Economics, Finance & Accounting, 2024)
Fashion is an inseparable part of daily appearance and style and every country has its own fashion and fashion is able to change the country's economy. The purpose of this study was to determine the effect of price perception on life style, to determine the effect of life style on purchasing decisions and to determine the effect of price perception in mediating the relationship between life style and purchasing decisions. The method used in this research is descriptive and associative method through quantitative approach. The population in this study were residents of Sukabumi City who use Uniqlo. The sample used in this study amounted to 200 people. The sample was taken based on Malhotra's theory, that a minimum communality of 0.5 must be estimated with a sample of at least 200. The research data used in this study include primary data and secondary data, namely observation, interviews, questionnaires, literature studies, and documentation. The results of this study Lifestyle has a direct and significant effect on price perception on Uniqlo users in Sukabumi City. Price perception has a direct and significant effect on purchasing decisions for Uniqlo users in Sukabumi City. Price perception mediates the relationship between lifestyle and purchasing decisions for Uniqlo users in Sukabumi City.